Analisis Efisiensi Saluran Distribusi Tembakau Virginia (Studi Kasus Penjualan Daun Basah dan Kering Rajangan di Desa Sumberharjo Bojonegoro) - Juwartini Juwartini; Darsan Darsan; Fina Sulistiya Ningsih (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
Tobacco is a plantation commodity that is widely cultivated in Sumberharjo Village. There are two types of tobacco for farmers to market: wet-leaf and dry-shredded leaf. This study was conducted to determine the optimal distribution channel for Virginia tobacco products in various forms. The research was conducted in October-November 2024 in Sumberharjo Village. The sample of respondents in this study consisted of 40 tobacco farmers, using randomly selected farmer samples, while the marketing institution samples were obtained through the snowball technique. The variables in this study were the selling price, the purchase price, and the marketing costs of Virginia tobacco. The data analysis used included marketing margin analysis to determine how large the marketing margin is in the distribution channel. The farmer's share analysis is intended to determine how much of the price the farmers own, and a marketing efficiency analysis is used to determine the most efficient distribution channel that will benefit the farmers. The results of the research show that the channel of 2 dry leaves of tobacco (farmers-wholesalers-warehouses) produces the highest farmer's share, so that farmers get the most significant portion of the added value of the product, namely 95%, and the smallest efficiency value, namely 0.406%. Farmers need to do profitable farming by selling in the most efficient distribution channel so that farmers receive high income.